Pelatihan Pengelolaan Website Desa - Ade Surahman; Tri Darma Rosmala Sari; Lili Andraini; Izudin Ismail (Universitas Teknokrat Indonesia, 2023)
Panggungrejo is a village in the Sukoharjo District, Pringsewu Regency, Lampung Province, Indonesia. This village has an area of 450 hectares. The majority of the livelihoods of Pekon Panggung Rejo residents are farmers, chicken breeders, red cattle breeders and traders. Apart from that, there are also residents who work as civil servants, the TNI and masons, other residents work as laborers managing oil palm and rubber. Panggung Rejo Village has the potential to become a tourist village because of its natural beauty. Based on interviews conducted with the head of Pekon Panggung Rejo, it was found that the problem being faced by partners was that the village website operator changed assignments and domiciles, so that the management of the village website stopped, because there were no village officials who could operate the website. Therefore, the PKM team from the Indonesian Technocrat University provided training on creating and managing Village websites, including Facebook and IG, as well as training on basic computer knowledge such as Microsoft Word and Microsoft Excel for Village officials, so as to make it easier for the community to find information and services. Village. The expected outputs from this PKM activity are scientific articles published in community service journals, and news published in newspapers. The activity was carried out for 6 months, starting in early July and ending in December 2021.